Neurocutaneous melanosis presented with giant congenital melanocytic nevi and primary intracranial melanoma - Shakya, Anup; Huang, Jinbai (Journal of Kathmandu Medical College, 2016)
Neurocutaneous melanosis is a rare neurocutaneous syndrome defi ned by the presence of multiple and /or giant congenital cutaneous nevi and melanocytic deposits in the central nervous system with the infi ltration of leptomeninges. The major medical concern with giant congenital cutaneous nevi is high risk of developing cutaneous melanoma, leptomeningeal melanoma, and neurocutaneous melanosis. Neurological symptoms usually develop before 2 years of age, but rare in the second or third decades of life. A 24-year-old-man with giant hairy, pigmented nevus on his extremities, back, “bathing trunk” variety presented with onset of neurological symptoms only in second decade of life. Magnetic resonance imaging of brain revealed a large expansive lesion in the left parieto-occipital lobe with high intensity on T1- sequence, and was heterogeneous on T2-sequence with iso- and hyper intense areas. Post-surgical pathological diagnosis revealed characteristics of malignant melanoma. Our patient represents a rare association between neurocutaneous melanosis with giant congenital cutaneous nevi and development of primary intracranial melanoma with neurological symptoms appearing in adult life. The onset of neurological symptoms only in third decade of life in our patient illustrates the importance of recognizing the likelihood of neurocutaneous melanosis in children with giant congenital nevus with or without neurological symptoms.Journal of Kathmandu Medical College, Vol. 4(1) 2015, 29-33